Finders Keepers A Novel - King, Stephen 1947 (New York Scribner, 2015)
Wake up, genius. So announces deranged fan Morris Bellamy to iconic author John Rothstein, who once created the famous character Jimmy Gold and hasn't released anything since. Morris is livid, not just because his favorite writer has stopped publishing, but because Jimmy Gold ended up as a sellout. Morris kills his idol and empties his safe of cash, but the real haul is a collection of notebooks containing John Rothstein's unpublished work - including at least one more Jimmy Gold novel. Morris hides everything away before being locked up for another horrific crime. But upon Morris's release thirty-five years later, he's about to discover that teenager Pete Saubers has already found the stolen treasure -- and no one but former police detective Bill Hodges, along with his trusted associates Holly Gibney and Jerome Robinson, stands in the way of his vengeance.
"A masterful, intensely suspenseful novel about a reader whose obsession with a reclusive writer goes far too far -- a book about the power of storytelling, starring the same trio of unlikely and winning heroes King introduced in Mr. Mercedes" -- ""Wake up, genius." So begins King's instantly riveting story about a vengeful reader. The genius is John Rothstein, an iconic author who created a famous character, Jimmy Gold, but who hasn't published a book for decades. Morris Bellamy is livid, not just because Rothstein has stopped providing books, but because the nonconformist Jimmy Gold has sold out for a career in advertising. Morris kills Rothstein and empties his safe of cash, yes, but the real treasure is a trove of notebooks containing at least one more Gold novel. Morris hides the money and the notebooks, and then he is locked away for another crime. Decades later, a boy named Pete Saubers finds the treasure, and now it is Pete and his family that Bill Hodges, Holly Gibney, and Jerome Robinson must rescue from the ever-more deranged and vengeful Morris when he's released from prison after thirty-five years."
CATALOGED FROM VENDOR RECORD. SUBJECT TO CHANGE.-"A masterful, intensely suspenseful novel about a reader whose obsession with a reclusive writer goes far too far -- a book about the power of storytelling, starring the same trio of unlikely and winning heroes King introduced in Mr. Mercedes" -- ""Wake up, genius." So begins King's instantly riveting story about a vengeful reader. The genius is John Rothstein, an iconic author who created a famous character, Jimmy Gold, but who hasn't published a book for decades. Morris Bellamy is livid, not just because Rothstein has stopped providing books, but because the nonconformist Jimmy Gold has sold out for a career in advertising. Morris kills Rothstein and empties his safe of cash, yes, but the real treasure is a trove of notebooks containing at least one more Gold novel. Morris hides the money and the notebooks, and then he is locked away for another crime. Decades later, a boy named Pete Saubers finds the treasure, and now it is Pete and his family that Bill Hodges, Holly Gibney, and Jerome Robinson must rescue from the ever-more deranged and vengeful Morris when he's released from prison after thirty-five years."
114290
Keywords: 2000-2099; Authors; Fans (Persons) -- Fiction; Psychopaths -- Fiction; Secrecy -- Fiction; Mental illness -- Fiction; Suspense fiction